The degree of practicing administrative creativity methods in kindergarten institutions From the point of view of parameters A field study in Riyadh, Lattakia city: The degree of practicing administrative creativity methods in kindergarten institutions From the point of view of parameters A field study in Riyadh, Lattakia city (Journal of Hama University, 2024)
The research aims to investigate the degree of practice of administrative creativity methods in kindergarten institutions from the point of view of female teachers in the city of Lattakia.the point of view of the research sample is defined according to the variables (years of service, academic qualification, educational qualification).The research sample included (108) female teachers for the academic year 2022-2023, to achieve the goal of the for the research, a questionnaire was designed that contained (20) phrases devoted to methods of administrative creativity, it was distributed on (2) axis (the brainstorming method, the influential factors analyzing method), the resuIts showed that the degree of practicing administrative creativity methods among female managers was significant for the questionnaire (4.40). The resuIts aIso showed that it has a high degree in each of the two areas of administrative creativity, as the averages ranged between (4.39% - 4.42%). the method of analyzing the influence factors came in the first place (4.42%) and the brainstorming method came in the second place (4.39%), It also showed that there were no significant differences according to the variables (years of service, academic qualification, educational qualification), the research ,presented many proposals, including giving administrative creativity and its methods importance by the Ministry of Education and its principais, holding training courses and seminars to train female teachers and develop their creative level and work for the better, both before and during the service period, in order to develop and improve the institution work for the better.
Keywords: administrative creativity - kindergarten teachers